Ministerial Decree No. 93/2013 Concerning The Obligation To Produce According To The Egyptian Standard Specifications - egypt (2025)
Ministry of Industry and foreign trade decree no. 93 of the year 2013 – attachment of the ministerial decree no. 93 of the year 2013 وزارة الصناعة والتجارة الخارجية قرار رقم 93 لسنة 2013 – مرفق القرار الوزارى رقم 93 لسنة 2013